Unveiling hidden rocky reefs of the Mexican Atlantic coast: Topographic characterization and benthic community dynamics along the North Coast of the Yucatan Peninsula, Mexico - Ileana Ortegón-Aznar; Johnny Omar Valdez-Iuit; Armin N. Tuz-Sulub; Alain Duran (PLoS ONE, 2026)
Rocky reefs are vital ecosystems hosting diverse benthic communities, including sessile organisms like algae, octocorals, and sponges, alongside associated fish and invertebrates, providing numerous ecosystem services. Despite their ecological significance, rocky reefs along the Mexican Atlantic coast remain understudied. This study presents a comprehensive topographic and ecological analysis of four rocky reef sites along the Yucatan Peninsula: Dzilam (La Poza and Small Mountain Range), Telchac, Progreso, and Chicxulub. Using bathymetric surveys, reef structures were mapped, and underwater surveys analyzed the benthic composition. Bathymetric surveys revealed distinct structural morphologies and rugosity indices, while sediment analysis identified varying grain sizes influencing benthic community composition. Macroalgae dominated the benthic cover (64%), followed by long sediment-laden algal turf-(LSAT, 21%) and sessile invertebrates (e.g., sponges). A strong negative correlation (r = −0.754, P < 0.0001) between macroalgal abundance and LSAT highlights competitive dynamics, modulated by environmental factors such as depth, sediment type, and topographic complexity. This study is the first report of the presence of rocky reefs in Yucatan and Mexican Atlantic coast, these findings underscore the ecological significance of rocky reefs as biodiversity hotspots and their sensitivity to substrate characteristics. This study highlights the need for further spatiotemporal research to understand their ecological dynamics and inform conservation strategies.